Кримінально-правові проблеми встановлення покарання за безгосподарське використання земель - Цвіркун, Н. Ю.; Tsvirkun, N. Y.; ORCID: http://orcid.org/0000-0001-9195-3349 (Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 155-167., 2015)
Статтю присвячено проблемі встановлення кримінально-правового покарання за безгосподарське використання земель. Здійснено кримінально-правовий аналіз шляхом порівняння санкцій за злочини у сфері землекористування в інших країнах зі схожими соціально-правовими умовами та екологічним станом. Зважаючи на великий обсяг екологічної, економічної шкоди від безгосподарського використання земель та можливості впливу на свідомість винного за допомогою обмежень економічного характеру, доцільним визнається застосування покарання у вигляді штрафу, а недоцільними – лише покарання, що пов’язані з ізоляцією винного від суспільства, враховуючи сучасні тенденції до гуманізації системи покарання.

It is human nature not only follow, but also violate the law, he makes it consciously or unconsciously, with intent or negligence. In this regard, each country has a system of measures that protects each person individually and the society in the whole from offenders and restores the justice. If a person does not want to obey the law and does not fulfill its requirements, the adequate response of the law is criminal prosecution and punishment. Independent form of realizing criminal liability for careless use of lands is state condemnation of a perpetrator of sentencing and its subsequent execution, which is differentiated by the degree of public danger of criminal assault. Thus, for committing a socially dangerous act under the Art. 254 of the Criminal Code of Ukraine alternative penalty in the form of a fine up to two hundred and fifty thousand tax-free minimum incomes of citizens or imprisonment for a term of two years with deprivation of the right to occupy certain positions or engagement in certain activities for up to three years or without it is provided. It is very difficult to make conclusions about the proportionality of specific sanctions, because the theory of sanctions in domestic criminal law doctrine is still not developed enough. The doctrines of other countries do not contain its completed form, too. The situation is more complicated regarding a crime under the Art. 254 of the Criminal Code of Ukraine because of a rare court practice of this category of cases. It is appropriate to compare the sanction of the Art. 254 of the Criminal Code of Ukraine with the criminal legislation of foreign countries with similar social and legal conditions and environmental condition. Conducted analysis of sanctions of the articles, which assume liability for crimes in the sphere of land use under the Criminal Code of other countries, demonstrates that in the most cases rather strict sanctions are set for their commission, taking into consideration that almost all articles of the Criminal Code of foreign countries, which are being researched, unlike the Art. 254 of the Criminal Code of Ukraine have qualified corpus delicti. They mainly refer to the serious consequences for the environment and society, and provide punishment in the form of imprisonment for a specified period. The Criminal Code of Ukraine provides such penalties for committing careless use of lands as: 1) a fine that is provided a major penalty by the sanction of the Art. 254. This situation is fair and appropriate to restore the quality of the soil cover (hence its use value) due to careless use of lands the state needs a lot of money and its high dimensions have to some extent encourage landowners and land users to protect and rational use of lands; 2) restriction of liberty, which, of course, is less severe form of punishment, compared to imprisonment, and most likely inappropriate in this case. Thus it is offered to use this kind of punishment only if there is a threat of re-offending; 3) deprivation of the right to occupy certain positions or engagement in certain activities is an appropriate form of punishment for this article and additional form of punishment, when a special subject of careless use of lands is an official, who was responsible for the protect and rational use of land resources. Establishment of this type of punishment for committing careless use of lands is entirely caused because there is a clear need for the deprivation of a certain person from the position or activities, through which he harms the quality of soil and the environment in general. To harmonize the sanction for careless use of lands it is appropriate to increase the fines and introduction of confiscation proper to the perpetrator of a land or termination of his right to use the land, which he has obtained for rent or use.

Статья посвящена уголовно-правовой проблеме установления наказания за бесхозяйственное использование земель. Осуществлен уголовно-правовой анализ путем сравнения санкций за преступления в сфере землепользования в других странах с похожими социально-правовыми условиями и экологическим состоянием. Учитывая большой объем экологического, экономического вреда от бесхозяйственного использования земель и возможности воздействия на сознание виновного с помощью ограничений экономического характера, целесообразным признается применение наказания в виде штрафа. Нецелесообразными в свете современных тенденций к гуманизации системы наказания считаются только те, что связаны с изоляцией виновного от общества.
Цвіркун, Н. Ю. Кримінально-правові проблеми встановлення покарання за безгосподарське використання земель // Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 155-167.
Цвіркун Н. Ю. "Кримінально-правові проблеми встановлення покарання за безгосподарське використання земель." Вісник Кримінологічної асоціації України 2 (2015): 155-167.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; безгосподарське використання земель; покарання; штраф; конфіскація; careless use of lands; penalties; fine; confiscation; бесхозяйственное использование земель; наказание; конфискация